Condición afectiva en adultos mayores de más de 60 años, pertenecientes al grupo salud y vida, del centro de salud El Blanqueado, entre diciembre del 2015 y marzo del 2016 - Simbaña Guallichico, Lucía Fernanda (2016)
The present investigation had as objective investigate the affective condition of the elderly of the group “salud y vida” the health center El Blanqueado during the period December 2015-march 2016. It is considered that around of the 60 years in advance, it produce a series of losses and biopsychosocial changes that every person experiences in a particular way. Some of these losses can result in states of loneliness, experienced in some cases with unpleasant feelings, accompanied by anxiety and depression. The investigation used the quantitative methodology, through of the use of the following reactive: the scale structure loss in the elderly, Scale of loneliness in the elderly IMSOL-AM, State-Trait Anxiety Inventory, STAI and Beck Depression Inventory (BDI -II). The results obtained show moderate levels of losses, among which are: the loss of economic resources, the loss of self-confidence and be useful. The loneliness as condition (alignment familial) and as sentiments of dissatisfaction is experimented by around of de half of group. However referring information to the presence of anxiety and depression reached light levels or minimums. These results show that the emotional condition hasn`t been significantly impaired. Apparently elements resilience acts as belief in a higher power and influence of the group space as protective factors.